2019
DOI: 10.1111/ene.13893
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography represents a sensitive and reliable tool for routine monitoring of idiopathic intracranial hypertension with and without papilledema

Abstract: Background and purpose We previously reported that certain optical coherence tomography (OCT) measures were sensitive and reliable in identifying idiopathic intracranial hypertension (IIH). This prospective study aimed to define OCT measures that allow differentiation of IIH with and without papilledema, thereby helping clinical decision‐making. Methods Eight patients with IIH with papilledema, nine without papilledema and 19 with other neurological diseases were included. OCT measures were obtained before lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Our results showed that GCIPL is more stable, with less deviation. GCIPL is less affected by papilledema or disk swelling 37 . In acute ON, RNFL undergoes pseudo‐thinning which can last 3‐9 months before real thinning can be demonstrated 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that GCIPL is more stable, with less deviation. GCIPL is less affected by papilledema or disk swelling 37 . In acute ON, RNFL undergoes pseudo‐thinning which can last 3‐9 months before real thinning can be demonstrated 38 .…”
Section: Discussionmentioning
confidence: 99%
“…10 There is a paucity of precisely sensitive and objective indicators of the disease for monitoring relapses and remission. 11,12 Moreover, no sensitive and objective methods have been established yet to determine the disease severity in order to decide whether surgery should be performed in these patients. [12][13][14] Despite the potential of IIH to cause visual morbidity, only a limited number of studies are available in the literature to predict the potential impact of IIH on the vision.…”
mentioning
confidence: 99%
“…11,12 Moreover, no sensitive and objective methods have been established yet to determine the disease severity in order to decide whether surgery should be performed in these patients. [12][13][14] Despite the potential of IIH to cause visual morbidity, only a limited number of studies are available in the literature to predict the potential impact of IIH on the vision. 13 The findings obtained by VEP reflect the functions of the visual pathways extending from the retina to the occipital cortex.…”
mentioning
confidence: 99%
“…Retinal correlates have been observed in a range of some of the most common neurological disorders, some of which are not commonly associated with visual symptoms. Further to those conditions discussed, retinal correlates have been found in other neurological diseases such as idiopathic intracranial hypertension (IIH), 348 chronic migraines, 349351 and a range of psychiatric conditions. 352,353 The majority of evidence exists in the form of cross-sectional studies comparing disease groups and healthy controls; however, further work must be done to take advantage of the unique opportunity the eye provides to serially image subjects through time.…”
Section: Resultsmentioning
confidence: 96%